Manakamana Temple Tourism - Adhikari, Shyamchandra (Research Nepal Journal of Development Studies, 2020)
Many tourists from India specially visit Nepal for religious purpose. This study has been concentrated on religious tourism and its socio economic impacts in Manakamana. Manakamana temple is one of the important religious site of Nepal located in Gorkha district around 104 KM far from the Kathmandu. After establishment of the cable car in 2001 by Manakamana Drashan Private Limited, had brought changing dimension in the pilgrimage tourism. There can be seen both positive and negative impacts of the cable car. It is being the center of attraction of the tourist to visit Manakamana. It has increased and tourism related activities jump a long step in the area, however, the cable car had directly hit the traditional business like horse riding business, moles, donkeys, used as porter activities and so on. In this connection how and why pilgrimage tourism brings socio economic changes in Manakamana area as well as what types of negative and positive impacts. This study is based on both primary and secondary data and followed qualitative research design. For this study data were collected by using observation and individual questionnaires.